The use of activated charcoal toothpaste as a tooth whitener and its consequences (Research, Society and Development, 2022)
One of the biggest concerns of dental professionals regarding the use of activated charcoal-based toothpastes, is how harmful this product is to individuals who use it routinely. Behind these products, a marketing is produced propagating a false effectiveness of these toothpastes, where they promise effective whitening and quick results. With this, people end up having a pretense that their teeth will whiten with brushing, and end up putting the dental enamel at risk, and it is possible that damage to the periodontium can occur, cavities can arise, or even pigmentation in the teeth. With the excessive growth of toothpastes with activated charcoal in their composition and of people who use them, it is necessary that dental surgeons be able to make their patients be more careful with products that are not effective and that perform tooth whitening in the dental office, making the treatment safe and well performed.